Penerapan model pembelajaran assurance, relevance, interest, assessment, satisfaction (arias) untuk meningkatkan keterampilan pemecahan masalah soal cerita peserta didik kelas v sekolah dasar - Harintya, Tiara Esti; Mulyono, Hadi; Suharno, Suharno (Universitas Sebelas Maret, 2019)
The aim of this research is to improve the word problem solving skills through the use of learning models Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS). This is an action classroom research that carried out for two cycles. Every cycle consist of four steps there are planning, implementation, observation, and reflection. Technique that uses for collect data are observation, interview, test, and documentation. The data validity test technique used content validity and triangulation. The data analysis technique uses interactive model learning. The result of this research showed that the initial pre-action test score were 47.08 with classical completeness of 15.15%, increased in the first cycle by 69,2 with classical completeness of 51.5%, then in second cycle it increased significantly to 81.06 with classical completeness of 81.82%. Referring to the results of this reserch it can be conclude that the use of ARIAS learning models can improve the word problem solving skills in fifth grades students of SDN Bumi I No.67 Surakarta academic year 2018/2019.